Ensuring Electoral Integrity Through Professional and Ethical Election Organizers - Jaidun, Jaidun; Jaang, Syaharie (Indonesian Journal of Public Policy Review, 2024)
General Background: The integrity of a nation's leadership is fundamentally shaped by the credibility of its electoral process. A free, secret, and fair presidential election ensures the emergence of leaders who govern with professionalism, transparency, and accountability. However, the effectiveness of electoral institutions is often compromised by political influence and material interests. Specific Background: In Indonesia, electoral integrity is upheld by institutions such as the General Election Commission (KPU), the Election Supervisory Body (BAWASLU), and the Honorary Council for General Election Organizers (DKPP). Despite their mandate, these institutions face significant challenges related to political interference, which undermines their ability to conduct elections transparently and fairly. Knowledge Gap: While numerous studies have examined election integrity, limited research specifically addresses the moral and professional challenges faced by electoral institutions in Indonesia. The extent to which political and economic pressures affect the neutrality of election organizers remains an area requiring deeper investigation. Aims: This study aims to analyze the professionalism of electoral organizers in Indonesia’s presidential elections by assessing legal frameworks, ethical considerations, and institutional challenges. Results: Findings indicate that electoral officials must uphold strong moral principles and legal accountability to withstand internal and external pressures. Ensuring free and fair elections requires institutional integrity, which is currently threatened by undue influence from powerful political entities. Novelty: This research highlights the ethical dilemmas faced by election organizers, emphasizing the need for robust legal and institutional safeguards to protect electoral integrity. Unlike previous studies, it provides an in-depth analysis of both internal and external challenges affecting electoral professionalism. Implications: Strengthening legal mechanisms and enhancing institutional independence are crucial to maintaining the credibility of electoral processes. This study underscores the necessity of professional and ethical electoral organizers in fostering democratic governance and national stability. Highlights: Electoral Integrity – Fair elections ensure accountable and transparent leadership. Institutional Challenges – Political influence threatens election organizers’ neutrality. Strengthening Governance – Legal safeguards protect democracy and electoral integrity. Keywords: Electoral integrity, election organizers, political interference, professional ethics, democratic governance.